Private Equity Acquisitions of Physician Medical Groups Across Specialties, 2013-2016 - Zhu, Jane M. (JAMA, 2020)
This study characterizes practice characteristics and specialties of physicians and medical groups acquired by private equity firms between 2013 and 2016.